PENGEMBANGAN JARINGAN KOMPUTER NIRKABEL (WiFi) MENGGUNAKAN MIKROTIK ROUTER (STUDI KASUS PADA SMA PGRI AIKMEL) - Lalu Delsi Samsumar; Sofian Hadi (Universitas Methodist Indonesia, 2018)
Information technology has penetrated into various fields including educational institutions, then the need for information is currently increasing. Currently everyone needs information in a fast, short and accurate time, therefore it takes media and tools that can support the work with various applications, media, and easy ways to access the information, one of them is internet connection with hotspot service or wireless-based computer network (WiFi). SMA PGRI Aikmel is one of the private schools that have many enthusiasts because it has adequate facilities in conducting teaching and learning process. Along with the increase of public trust to this educational institution, hence required a wireless based computer network to support performance at academic part and to improve teaching and learning activity. By leveraging rapid technological advancements to enable equipment using cable technology to be replaced with wireless technology such as radio frequency media. This research is a qualitative research. Data were collected by observation, interview, documentation, and literature study. With the Network Development Live Cycle (NDLC) method, this study examines the development of wireless networks using Mikrotik devices and cisco packet tracer applications as simulation media from the development of network schemes.